SCALE EFFICIENCY IN TAMBAQUI FARMING IN EARTH PONDS IN THE METROPOLITAN REGION OF MANAUS-AM - Costa, Jesaias Ismael da [UNESP]; Sabbag, Omar Jorge [UNESP]; Geraldo Martins, Maria Inez Espagnoli [UNESP] (Inst Pesca, 2020)
This study aimed at determining the scale efficiency in tambaqui production in earth ponds developed in the metropolitan region of Manaus-AM. Eleven fish farms were analyzed and their data were sampled regarding its characteristics, productive data, disbursement, infrastructure value and production value, in order to calculate the total operational cost and profitability indexes. For the DEA (Data Envelopment Analysis) was applied the VRS/BCC (variable return of scale) model with input orientation, using three inputs (total operational cost, feed value, and depreciation, all in BRL($) per kilo) and one output (annual gross revenue, in BRL($) per hectare). The study showed that 80% of the fish farms (DMUs) (decision-making units) had increasing returns to scale, with scale efficiencies lower than 65%, affected by lack of profitability, low technical and marketing knowledge, high production cost (R$ 4.50 kg(-1)) and low average sales price (lower than R$ 5.00 kg(-1)).
Keywords: Colossoma macropomum; data envelopment analysis; production cost; decision making; fish farming